How can micelle systems be rebuilt by a heating process? - da Silva-Filho, Miguel Adelino; Siqueira, Scheyla Daniela Vieira da Silva; Freire, Larissa Bandeira; de Araújo, Ivonete Batista; de Holandae e Silva, Káttya Gyselle; da Medeiros, Aldo Cunha; Araújo-Filho, Irami; de Oliveira, Anselmo Gomes [UNESP]; do Egito, Eryvaldo Sócrates Tabosa (My University, 2012)
The aim of this work was to evaluate how an aqueous micellar system containing Amphotericin B (AmB) and sodium deoxycholate (DOC) can be rebuilt after heating treatment. Also, a review of the literature on the physicochemical and biological properties of this new system was conducted. Heated (AmB-DOC-H) and unheated (AmB-DOC) micelles were then diluted at four different concentrations (50 mg. L -1, 5 mg. L -1, 0.5 mg. L -1, and 0.05 mg. L -1) to perform physicochemical studies and a pharmacotoxicity assay, in which two cell models were used for the in vitro experiments: red blood cells (RBC) from human donors and Candida parapsilosis (Cp). While potassium (K +) and hemoglobin leakage from RBC were the parameters used to evaluate acute and chronic toxicity, respectively, the effcacy of AmB-DOC and AmB-DOC-H were assessed by K + leakage and cell survival rate from Cp. The spectral study revealed a slight change in the AmB-DOC aggregate peak from 327 nm to 323 nm, which is the peak for AmB-DOC-H. Although AmB-DOC and AmB-DOC-H exhibited different behavior for hemoglobin leakage, AmB-DOC produced higher leakage than AmB-DOC-H at high concentrations (from 5 mg. L -1). For K + leakage, both AmB-DOC and AmB-DOC-H showed a similar profle for both cell models, RBC and Cp (P < 0.05). AmB-DOC-H and AmB-DOC also revealed a similar profle of activity against Cp with an equivalent survival rate. In short, AmB-DOC-H showed much less toxicity than AmB-DOC, but remained as active as AmB-DOC against fungal cells. The results highlight the importance of this new procedure as a simple, inexpensive, and safe way to produce a new kind of micelle system for the treatment of systemic fungal infections. © 2012 Silva-Filho et al.
Keywords: Micelles; Nanotechnology; Pre-heated amphotericin B; Super-aggregates